Distribution of a Taxi Fleet: The Problem of Arranging Repair and Maintenance in the Absence of Centralized Management - Eugeniu Cozac; Mikhail Gordienko; Mikhail Bogdanov; Tatyana Sakulyeva; Ilia Aksenov (Automotive Experiences, 2021)
The article presents a mathematical model for distributed taxi fleet operations. A technological approach based on mathematical models of transport systems using the Hungarian algorithm was used to model the arrangement of repair and maintenance in the absence of centralized management. The literature review on taxi fleet robotics has shown that central management is the cause of increasing transport service costs up to 30%. The results of approximating the cases of repairing and maintaining the taxi fleet in the absence of centralization to the lognormal and Gaussian distributions are provided based on 2019-2020 data. A blockchain scheme for work organization and maintenance of the taxi fleet within the decentralization framework is developed. The statistical analysis of repair and emergency maintenance cases in the distributed taxi fleets calculated per 1000 cars was 3.6 to 15%. Pearson's criterion c2 was from 0.001 to 0.17. Statistical significance values of the results were p≤0.005. A multivariate cluster analysis of the accident or technical failure occurrence among the distributed taxi fleet vehicles was conducted in months, taking statistical data for the last two years. An algorithm that allows performing optimal assignments for a distributed taxi fleet is developed in this work. A sample calculation of the optimal allocation for taxi fleet vehicles distributed in the state of minimum vehicle repair cost based on the Hungarian algorithm was provided. The application of this algorithm also makes it possible to determine the optimal destinations for vehicles in the taxi fleet.